A nonovershooting tracking controller for simultaneous infusion of anesthetics and analgesics. (March 2019) - Padmanabhan, Regina; Meskin, Nader; Ionescu, Clara M.; Haddad, Wassim M.
Highlights: Measured outputs are used to track desired outputs without incurring an overshoot. The proposed method is particularly suitable for the control of MIMO drug infusion. The integral action in the controller design helps to achieve robust tracking. Abstract: In this paper, a nonovershooting tracking controller is proposed for the continuous infusion of multiple drugs that have interactive effects. The proposed controller design method exploits the freedom of eigenstructure assignment pertinent to the design of feedback controllers for multi-input, multi-output (MIMO) systems. For drug dosing, a nonovershooting tracking controller restricts the undesirable side effects of drug overdosing. The proposed tracking controller is based on an estimate of the full state using a hybrid extended Kalman filter (EKF) that is used to reconstruct the system states from the measurable system outputs. To illustrate the proposed method, we use one of the common anesthetic and analgesic drug combinations (i.e., propofol and remifentanil) which exhibit nonlinear and synergistic drug interaction. An integral control action is included in the controller design to achieve robust tracking in the presence of patient parameter uncertainty. Simulation results and performance analysis of the proposed control strategy are also presented using 20 simulated patients.